’Il grumo che resta sui polpastrellui’: Resisting angels in the poetry of Eugenio Montale - Riccobono, Rossella (Spunti e Ricerche, 2016)
In the first part of his poetic production Montale’s main thrust was towards an a priori impossible philosophical search for the "truth" beyond the spatio-temporal-historical boundaries of reality. On the other hand the "second Montale" is more preoccupied with the poetic observation of the surrounding reality: his gaze lowers itself to reality itself, seen as the "palta" where the poetic-ontological search identifies with a series of little "truths".